2019
DOI: 10.1101/531517
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ATAC-seq signal processing and recurrent neural networks can identify RNA polymerase activity

Abstract: Nascent transcription assays are the current gold standard for identifying regions of active transcription, including markers for functional transcription factor (TF) binding. Here we present a signal processingbased model to determine regions of active transcription genome-wide using the simpler assay for transposase-accessible chromatin, followed by high-throughput sequencing (ATAC-seq). The focus of this study is twofold: First, we perform a frequency space analysis of the "signal" generated from ATAC-seq e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The choice of a hybrid encoding scheme for each OCR fixed window resulted from a previous study [27], where we evaluated the performance of many different data encoding schemes and machine learning classifiers. OCRs were evaluated using only the signal at each nucleotide, only the underlying sequence, or a combination of both.…”
Section: Data Encodingmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of a hybrid encoding scheme for each OCR fixed window resulted from a previous study [27], where we evaluated the performance of many different data encoding schemes and machine learning classifiers. OCRs were evaluated using only the signal at each nucleotide, only the underlying sequence, or a combination of both.…”
Section: Data Encodingmentioning
confidence: 99%
“…We combined our sequence embedding and signal into a single vector representation (Fig 1a) that is utilized as input to the GRUs (Fig 1b). A learning rate of 0.0001, a dropout date of 0.1, an embedding layer size of 50 and a hidden layer size of 100 were selected after hyperparameter optimization, from a grid of embedding dimensions [15, 50, In a previous study [27] we evaluated a variety of classifiers and encodings for our RNN and found that the RNN outperformed all other methods at predicting histone marks associated with OCRs that are related to active transcription. For completeness, we briefly summarize the earlier study.…”
Section: Classifiersmentioning
confidence: 99%